Hubungan Curah Hujan, Pupuk Mop (Kcl) dan HGFB (Boron) Terhadap Produksi Kelapa Sawit (Elaeis guineensis Jacq.) Di Kebun Tabah Riau - Albatros Badrulina Al Kindi Saragih; Aisyah Lubis; Ahmad Sofian (Jurnal Agrofolium, 2026)
This study examines the effects of rainfall, MOP (KCl) fertilizer, HGFB (Boron) fertilizer, and their interactions on oil palm production at Tabah Estate, Riau. The research was carried out from May to July 2025 using simple and multiple linear regression. Results show that rainfall increases tons per hectare and first-semester bunch weight but reduces bunch number. MOP and HGFB fertilizers positively affect bunch weight but negatively affect production and bunch number. Their interaction significantly influences second-semester bunch weight and highly influences bunch number in both semesters. These findings highlight that oil palm productivity depends on combined climatic and fertilization factors, emphasizing the need for fertilizer adjustments aligned with rainfall patterns.